Innovating the science of agricultural development: 2025 state of the journal report - T. Grady Roberts; Amy Harder; James R. Lindner (Advancements in Agricultural Development)
This is the annual State of the Journal report for Advancements in Agricultural Development. 2024 was another great year for AAD. First, we formed a new partnership to elevate the digital presence of research published in AAD. Second, we published our first special issue. Third, we refined several policies to provide greater clarity for our authors. In this report, we also provide the journal statistics for 2024 and list all our reviewers for 2024.